Diagnostic performance comparison of the Chartis System and high‐resolution computerized tomography fissure analysis for planning endoscopic lung volume reduction. Issue 4 (25th February 2014) - Gompelmann, Daniela; Eberhardt, Ralf; Slebos, Dirk‐Jan; Brown, Matthew S.; Abtin, Fereidoun; Kim, Hyun J.; Holmes‐Higgin, Debby; Radhakrishnan, Sri; Herth, Felix J.F.; Goldin, Jonathan
Abstract Background and objective Endobronchial valve (EBV) therapy is optimized in patients who demonstrate little or no collateral ventilation (CV). The accuracy of the Chartis System and visual assessment of high‐resolution computerized tomography (HRCT) fissure completeness by a core radiology laboratory for classifying CV status was compared by evaluating the relationship of each method with target lobe volume reduction (TLVR) after EBV placement. Methods Retrospective HRCT fissure analysis of a study population who underwent catheter‐based measurement of CV followed by complete occlusion of the targeted lobe by EBV. Accuracy, sensitivity, specificity, positive predictive value and negative predictive value of the HRCT fissure analysis and the catheter‐based measurement of CV for predicting TLVR was determined. Results Accuracy for correctly classifying TLVR with EBV was similar for Chartis System and HRCT fissure analysis (74 vs 77%). The sensitivity and specificity of the Chartis measurement were 86% and 61% and those of HRCT fissure analysis 75% and 79%. Patients with TLVR ≥350 mL had statistically significant improvement in respiratory function, exercise performance and quality of life measures. Conclusions When evaluating patients for likelihood of successful EBV therapy, the Chartis System CV assessment and HRCT fissure analysis appear to have comparable accuracy. Both techniques were found to be beneficial for EBV procedure planning.